SANITARY AND HYGIENIC INSTITUTIONS OF OF RUSSIAN ZEMSKYI UNION DURING THE WORLD WAR I - Kovalska, G. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
The World War I, which began in 1914, from the very beginning gave a huge number of wounded and ill militarymen, caused a sharp deterioration in the sanitary state of the Russian Empire and caused the spread of epidemics both at the front and in the rear. The sanitary services of the country were not able to cope with these problems themselves. To help them came public charitable organizations, in particular, the most significant was the activities of the Russian Zemskyi Union (RZU). The purpose of the article is to analyze the creation and operation of the sanitary-hygienic institutions of the Zemskyi Union and to find out their role on the front. Among all sanitary and hygiene establishments of the RZU, organized at the front was the largest number of baths. In addition to the direct function to allow the militarymen to wash themselves out, they were mostly given to soldiers clean linen or instead of dirty or without replacement. Most of all baths were organized in special bath units, among which there were two types of establishments on the South-Western Front: advanced and rear. The task of each advanced bath unit was to serve the specific military unit of the corps, divisions and regiments. The rear bath units were attached not to military units, but to some locality. In some baths worked laundries, disinfection chambers and teahousesi. The work of disinfection chambers became a necessary complement to the sanitary activities of bathrooms. In addition, there were still independent disinfection units for the fight against epidemic diseases. Under the agreement with the military department, Zemskyi Union took over the work on the equipment of stage stations for teahouses, catering, baths, hairdressers and laundries and in the second half of January 1915 this work began. For military units located along the front lines, mobile baths and laundry were needed, and they were formed into body and diving bath units equipped with a convoy. Thus, sanitary and hygiene establishments of the RZU worked at the front and in the rear of the Russian Empire in parallel with the military sanitary department, and brought great benefit to the latter, completing its activities and helping him with the sanitary care of the army and the protection of his health. The sanitary facilities of the army were virtually powerless to protect it from infectious and epidemic diseases. Zemska sanitary organization in this regard revealed a great initiative and covered the nearest army rear with its network of sanitary and nutrition agencies. Among the sanitary facilities were disinfection units and cameras, baths, laundries and bacteriological laboratories that developed and produced vaccines for the control of infectious diseases.